Governance of Communication Networks Connecting Societies and Markets with IT - Preissl, Brigitte; Müller, Jürgen (Contributions to Economics, 2006)
Hardly anyone would doubt the potential of information technology (IT) to connect individuals, firms and organisations. Whether this power to connect will actually lead to the integration of markets and societies is a different issue. The articles collected in this book shed light on several aspects that are crucial for the success of global communication networks: they range from an appropriate framework for regulation and suitable strategies of firms that act as international players, to the inclusion of customers in defining product and service strategies, and from problems of access to advanced technology and networks for all groups in society regardless of their social status or geographical location to the role of new technologies in facilitating universal communication.